Analisis Kualitas Manajemen Dan Pertumbuhan Laba Terhadap Kinerja Saham Studi kasus pada PT. Berlian Laju Tanker, Tbk, PT. Bumi Recources, Tbk, dan PT. United Tractors, Tbk. - Soelehan, Aan; Christina, Syanti (Jurnal Ilmiah Ranggagading (JIR), 2008)
Share performance becomes company measurement in attaining work achievement. The share performance is reflected by share price. Customarily, market doers give appreciation on share based on company prospect for next time. Usually, the company prospect will be reflected by profit growth. Does profit growth raising mean share price raising? Does it mean wealth raising for the owner as well? Theoretically, it will be such as that. In this research, management quality with return on equity proxy obtained from net profit divided by capital average.. In case of profit growth, return on equity proxy multiplied by retention rate (b) where retention rate is fixed up from 1-dpo. Analysis and correlation & inter-variable influence method in this research utilizes correlation coefficient (R) and regression coefficient (B). The purpose of this research is to measure how far the influence of management quality toward companys share performance, how far the influence of profit growth toward share performance, and how the correlation between management quality and profit growth toward share performance will be. The outcome of this research shows that management quality has significant correlation and influence to share performance at BLTA and BUMI, but not such as that at UNTR. Its caused by the fact that UNTR has used more debt than finance capital. Profit growth has significant correlation and influence to BLTA and BUMI as well, but its not significant to UNTR due to change of share price. The correlation of management quality and profit growth is significant at the three companies. The significance level shows 90,7%, 84,2%, and 98,6% respectively. The main causal factor is bad governance by the management and also by external factor such as some rules from government and competition among the similar companies. Keywords: Profit growth to increase share performance.